Development of complex executive function over childhood: Longitudinal growth curve modeling of performance on the Groton Maze Learning Task. Issue 3 (2nd January 2023) - McGuckian, Thomas B.; Wilson, Peter H.; Johnston, Rich D.; Rahimi‐Golkhandan, Shahin; Piek, Jan; Green, Dido; Rogers, Jeffrey M.; Maruff, Paul; Steenbergen, Bert; Ruddock, Scott
Abstract: This longitudinal study modeled children's complex executive function (EF) development using the Groton Maze Learning Task (GMLT). Using a cohort‐sequential design, 147 children (61 males, 5.5–11 years) were recruited from six multicultural primary schools in Melbourne and Perth, Australia. Race/ethnicity data were not available. Children were assessed on the GMLT at 6‐month intervals over 2‐years between 2010 and 2012. Growth curve models describe age‐related change from 5.5 to 12.5 years old. Results showed a quadratic growth trajectory on each measure of error—that is, those that reflect visuospatial memory, executive control (or the ability to apply rules for action), and complex EF. The ability to apply rules for action, while a rate‐limiting factor in complex EF, develops rapidly over early‐to‐mid childhood.